Biosynthesis of lipid resorcinols and benzoquinones in isolated secretory plant root hairs - Dayan, Franck E (Journal of experimental botany, 2007)
The primary functions of root hairs are to increase the root surface area and to aid plants in water and nutrient uptake. However, some root hairs also have secretory functions and exude bioactive secondary metabolites. Sorghum (Sorghum bicolor) root hairs release a substantial amount of phenolic lipids including sorgoleone, a 3-pentadecatriene benzoquinone. The activity of the key enzymes involved in the biosynthesis of lipid resorcinols and benzoquinones was measured directly in isolated root hair preparations obtained from 6-d-old roots. The purified root hair preparation readily converted long-chain acyl-CoA starter units to their corresponding lipid resorcinols and decanoyl-CoA was the best substrate, yielding a 5-n-nonyl-resorcinol. The isolated root hair preparation also had high S-adenosyl-L-methionine-dependent O-methyltransferase activity, which catalyses the methylation of several 5-n-alkyl-resorcinols. Optimum activity was with 5-n-pentyl-resorcinol. Isolated root hairs also exhibited hydroxylase activity (putatively a P450 mono-oxygenase) that reacted with the lipophilic 5-pentadecyl-resorcinol substrate. The in situ hydroxylase activity was low relative to the other enzymes studied, but was still detectable in isolated root hairs. Thus, sorghum root hairs possess the entire metabolic machinery necessary for the biosynthesis of lipid resorcinols and benzoquinones. This will have implications for the genetic engineering of bioactive lipid resorcinols and benzoquinones in sorghum and in other plant species. It also demonstrates that some root hairs can function as specialized cells for the production of bioactive secondary metabolites